Observation of reconnection pulses by Cluster and Double Star - X. H. Deng; R. X. Tang; R. Nakamura; W. Baumjohann; T. L. Zhang; P. W. Daly; H. Rème; C. M. Carr; A. Balogh; Z. X. Liu; J. F. Wang (Annales Geophysicae, 2005)
During a reconnection event on 7 August 2004, Cluster and Double Star (TC-1) were near the neutral sheet and simultaneously detected the signatures of the reconnection pulses. AT 22:59 UT tailward flow followed by earthward flow was detected by Cluster at about 15 RE, while earthward plasma flow followed by tailward flow was observed by TC-1 at about 10 RE. During the flow reversal from tailward to earthward, the magnetic field Bz changed sign from mainly negative values to positive, and the X component of the magnetic curvature vector switched sign from the tailward direction to the earthward direction, which indicates that the reconnection site (X-line) moved tailward past the Cluster constellation. By using multi-point analysis and observation of energetic electron and ion flux, we study the movement and structure of the current sheet and discuss the braking effect of the earthward flow bursts in the inner magnetosphere.